The Land of Flowers - Stilton, Thea; Clement, Emily (New York : Scholastic Inc., 2017)
The Seven Roses, magical flowers which bloom forever and which are linked to the health of the Land of Flowers, are dying, and the Thea sisters together with Will Mystery must travel to that land to discover the reason--a journey where every flower seems determined to hinder their passage.
Geronimo Stilton.
3.4.
3-6.
600L
Keywords: Mice -- Fiction; Fairies -- Fiction; Flowers -- Fiction; Magic -- Fiction; Sisters -- Fiction; Quests (Expeditions) -- Fiction; Voyages and travels -- Fiction; Action and adventure fiction